Impact of a Functional Recovery Program on Ventilatory and Appendicular Muscles in Patients Post-Mechanical Ventilation for Covid-19; [Impacto de Un Programa de Recuperación Funcional en Músculos Ventilatorios y Apendiculares en Pacientes Post-Ventilación Mecánica por Covid-19] - Valenzuela-Vasquez, J; Del Valle-Valdes, M (Universidad de la Frontera, 2023)
SUMMARY: Patients with COVID-19 requiring mechanical ventilation (MV) evolve with functional consequences in the ventilatory and appendicular muscles that are not necessarily addressed in a differentiated manner. The objective of this research was to evaluate the impact of a functional recovery program in these patients and determine if the interventions differentially affect ventilatory functions and appendicular muscles, using low-cost tests. 47 patients with COVID-19 who were on MV were evaluated. After a baseline spirometry, they were performed; maximum inspiratory pressure (MIP), handgrip strength (HGS), sit to stand test (STST) and 6-minute walk test (6MWT), before and after the intervention plan. This program included supervised aerobic and strength exercises for two weekly 60-minute sessions for 3 months. After the program, significant improvements were observed in forced vital capacity (FVC), expiratory volume in the first second (FEV1) and MIP. Significant relationships were found between these measurements and the distance traveled of the 6MWT, the HGS and the STST. In conclusion, the functional recovery program in patients with COVID-19 who required MV benefits both ventilatory function and appendicular muscle strength. Appendicular muscle strength tests can be useful to evaluate recovery since they can provide differentiated information about your performances. Finally, more research is needed to better understand the response of these patients to rehabilitation. © 2023, Universidad de la Frontera. All rights reserved.